Preparation method and application of PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low-index crystal face structure

The PdNi alloy nanocrystal catalyst with high/low index crystal surface structure was prepared by solvent-thermal method and high-temperature calcination technology, which solved the problems of insufficient activity and poor stability of cathode oxygen reduction reaction catalysts in the existing fuel cell, and achieved efficient, stable and low-cost oxygen reduction reaction performance.

CN119725564APending Publication Date: 2025-03-28CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411734840.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing fuel cell cathode oxygen reduction catalysts have problems such as insufficient catalytic activity, poor stability and high cost, especially the scarcity of precious metal platinum and expensive, which limits its large-scale commercial application.

Method used

The PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high/low index crystal surface structure was prepared by solvent-thermal method and high-temperature calcination technology, and the microstructure of the catalyst was optimized to improve its oxygen reduction reaction performance.

Benefits of technology

The excellent oxygen reduction reaction activity and long-term stability of the catalyst are achieved, the preparation cost is reduced, the preparation process is simplified, and the preparation process is broad and commercial application prospects are broad.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725564A_ABST
    Figure CN119725564A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a PdNi alloy nanocrystalline oxygen reduction reaction catalyst with a high / low-index crystal face structure. Through crystal face structure engineering, a solvothermal method is combined with a high-temperature calcination technology, and the novel PdNi alloy nanocrystalline catalyst is prepared. In the process, directional transformation of a palladium crystal face from a low-index crystal face to a high-index crystal face is effectively promoted by introduction of nickel ions, and the nitrogen-doped carbon material is generated by pyrolysis of an iminodiacetonitrile organic ligand. The prepared PdNi alloy nanocrystalline catalyst not only has a unique high / low index crystal face structure, but also shows excellent physical properties and electrochemical properties. In a fuel cell cathode oxygen reduction reaction, the catalyst shows excellent electrocatalytic activity, excellent stability and an efficient four-electron reaction path, and shows wide practical application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the preparation and application of a fuel cell cathode oxygen reduction reaction catalyst, and in particular to the preparation and application of a PdNi alloy nanocrystalline oxygen reduction reaction catalyst with a high / low index crystal plane structure. Background Art

[0002] Faced with increasingly severe energy shortage and environmental pollution problems, anion exchange membrane fuel cells (AEMFC) have become a clean energy technology that has attracted much attention due to their low corrosion sensitivity, cost advantages and excellent anti-permeation performance. As an important cathode half-reaction in electrochemical energy conversion devices, the oxygen reduction reaction (ORR) has slow reaction kinetics, complex pathways and high catalyst costs, which have become the main obstacles to its large-scale commercialization. Therefore, the development of cathode oxygen reduction reaction catalysts with high catalytic activity, stability and selectivity has become a research hotspot in this field. At present, precious metal platinum is the most commonly used ORR catalyst due to its excellent catalytic performance. However, considering that platinum is expensive and scarce, and palladium has similar catalytic properties to platinum and is abundant in reserves, palladium is regarded as a potential substitute for platinum-based catalysts.

[0003] In terms of improving the electrocatalytic performance of nanocrystals, regulating the atomic arrangement and chemical composition is one of the important strategies. The microstructure of the catalyst can be optimized by adjusting the size, composition, morphology, crystal structure and exposed crystal face of the nanoparticles. For example, by introducing transition metals (M = Ni, Co, Fe, Mn, Cu, etc.) to form alloys with Pd, the strain effect and ligand effect can be used to regulate the d-band center position of Pd, thereby optimizing the adsorption strength of oxygen-containing intermediates and enhancing its ORR performance. In addition, studies have shown that the crystal face orientation of palladium plays a crucial role in the ORR activity. Therefore, constructing ORR catalysts with high-index faces (HIFs) has become the focus of current research. HIFs show significantly better catalytic activity and selectivity than low-index faces (LIFs) due to their high density of low-coordinated steps and edge atoms. For example, HIFs (such as (200), (211), (311) and (322)) not only have high intrinsic catalytic activity, but also can serve as O 2 It is an ideal platform for molecular adsorption and OO bond breaking. In addition, HIF-coated nanocrystals usually have superior catalytic performance due to the synergistic effect between HIF on the outer surface and LIF inside. The high density of low-coordinated atoms on the surface of HIF helps the adsorption and activation of molecular oxygen, while LIF promotes OH through weak binding force. - generation and release.

[0004] At present, common HIF preparation methods include stranski-krastanov growth, electrochemical replacement, addition of capping agents, adjustment of precipitation diffusion rate and dealloying. However, due to the high surface energy and thermodynamic instability of HIF, its crystal face growth is difficult to effectively control. In contrast, although LIFs are thermodynamically stable during growth, they are prone to irreversible surface reconstruction and formation of corresponding oxide layers during the ORR process in the high potential range. It is worth noting that HIFs composed of low-coordinated metal atoms can maintain surface order without changing the structure. However, the preparation of bimetallic Pd-based alloy nanocrystals with high / low index crystal face structures and the study of their oxygen reduction performance are still rarely reported. Therefore, the present invention proposes a method for preparing PdNi alloy nanocrystal catalysts based on high / low index crystal face synergy, which provides a new idea for the research and development of fuel cell catalysts. Summary of the invention

[0005] In view of this, the purpose of the present invention is first to provide a method for preparing a PdNi alloy nanocrystalline oxygen reduction reaction catalyst with a high / low index crystal plane structure. The prepared PdNi alloy nanocrystalline electrode material can provide excellent ORR performance and has broad application prospects.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] (1) Preparation of PdNi nanoparticles by solvothermal method;

[0008] (2) preparing a PdNi alloy nanocrystalline catalyst having a high / low index crystal plane structure by a high-temperature calcination method using the PdNi nanoparticles obtained in step (1);

[0009] In order to achieve the above object, the present invention provides the following technical solutions:

[0010] Furthermore, in step (1), a certain amount of carbon powder is first dispersed in a certain amount of organic solvent and stirred continuously, and then a certain amount of Pd, Ni metal precursor and reducing agent are added to the above solution and stirred continuously. Then, the completely uniformly dispersed suspension is transferred to a high-temperature reactor and placed in a blast drying oven for high-temperature reaction. Thereafter, the reactor is allowed to cool naturally, and the PdNi nanoparticles in the reactor are washed with ethanol and acetone and placed in a blast drying oven for drying.

[0011] Further, in step (2), the PdNi nanoparticles obtained in step (1) are placed in a tube furnace and heated at a certain heating rate under H 2 / Ar atmosphere at high temperature.

[0012] Furthermore, in the step 1), a certain amount of carbon powder is first added to an organic solvent under ultrasonic stirring, ultrasonicated for 15 to 30 minutes, and then stirred for 1 to 2 hours after ultrasonic dispersion to form a uniformly dispersed suspension.

[0013] Furthermore, in step 1), the Pd and Ni metal precursors used are Pd(acac) 2 and Ni(acac) 2 , the reducing agent is iminodiacetonitrile, and the organic solvent is benzyl alcohol.

[0014] Furthermore, the mass and volume ratio of the carbon powder and benzyl alcohol in step 1) is 3 to 3.6.

[0015] Furthermore, the stirring speed in step 1) is 1000 to 1200 rpm.

[0016] Further, the mass of the iminodiacetonitrile in step 1) is Pd(acac) 2 and Ni(acac) 2 1.3 to 2 times of Pd(acac) 2 and Ni(acac) 2 can be fully restored.

[0017] Further, in step 1), Pd(acac) is added 2 and Ni(acac) 2 The atomic ratio is (1~20):1.

[0018] Further, in step 1), iminodiacetonitrile, Pd(acac) 2 and Ni(acac) 2 The stirring speed is 1200-1600 rpm.

[0019] Furthermore, the suspension obtained in step 1) is transferred to a 25-100 mL stainless steel autoclave lined with polytetrafluoroethylene, placed in a forced air drying oven, and reacted at 130° C. to 160° C. for 5 to 7 hours.

[0020] Further, the PdNi nanoparticle intermediate obtained in step 1) is centrifuged at a speed of 8000 to 12000 rpm, and the supernatant is discarded;

[0021] Furthermore, in step 1), the bottom precipitate is washed with ethanol and acetone, ethanol is first added for ultrasonic treatment for 2 to 8 minutes, and then acetone is added for ultrasonic treatment for 2 to 8 minutes, and centrifugation is performed at a speed of 8000 to 12000 rpm, and the washing and purification is repeated 2 to 5 times.

[0022] Furthermore, in step 1), the volume ratio of ethanol to acetone is 0.75 to 1.5.

[0023] Furthermore, the purified product in step 1) is placed in a forced air drying oven, dried at 60-80° C. for 6-8 hours, and allowed to stand for 8-24 hours.

[0024] Furthermore, the high temperature calcination temperature in step 2) is 600-800° C., the annealing time is 3-6 hours, and the heating rate is 5-10° C. / min.

[0025] Further, the H in step 2) 2 H in the mixed gas of Ar 2 The ratio is 5 to 10 wt%.

[0026] Furthermore, the oxygen reduction reaction performance of PdNi alloy nanocrystalline electrode materials with high / low index crystal plane structures was tested.

[0027] The beneficial effect of the present invention is that the present invention synthesizes a novel PdNi alloy nanocrystalline oxygen reduction reaction catalyst with a high / low index crystal face structure by using a solvothermal method combined with a high temperature calcination technology through crystal face structure engineering. This type of catalyst material has excellent oxygen reduction reaction activity and long-term stability, and the preparation process is simple and convenient, the preparation conditions are relatively simple, and it is easy to commercialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to make the purpose, technical scheme and beneficial effects of the present invention clearer, the present invention takes metal precursors of Pd and Ni with different atomic ratios as an example to prepare PdNi alloy nanocrystalline oxygen reduction reaction catalysts with high / low index crystal plane structures and provides the following figures for illustration:

[0029] Figure 1 The XRD pattern of the PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure obtained in Example 1;

[0030] Figure 2 TEM image of the PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure obtained in Example 1;

[0031] Figure 3 The XPS image of the PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure obtained in Example 1;

[0032] Figure 4 CV graph of the PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure obtained in Example 1;

[0033] Figure 5This is a comparison chart of the LSV and ORR performance of the PdNi alloy nanocrystalline oxygen reduction reaction catalysts with different palladium and nickel ratios obtained in Example 1;

[0034] Figure 6 Multiple LSV graphs of the PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure obtained in Example 1;

[0035] Figure 7 The graph of the electron transfer number and hydrogen peroxide yield of the PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure obtained in Example 1 at a potential of 0.1 to 0.9 V;

[0036] Figure 8 The methanol permeation resistance diagram of the PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure obtained in Example 1;

[0037] Fig. 9 LSV graph of the PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure obtained in Example 1 before and after 10,000 accelerated durability tests. DETAILED DESCRIPTION

[0038] The preferred embodiments of the present invention are described in detail below. The experimental methods without specific conditions in the embodiments are usually carried out under conventional conditions or under conditions recommended by the manufacturers.

[0039] Example 1

[0040] Taking the atomic ratio of Pd to Ni as 10:1 as an example, the preparation of PdNi alloy nanocrystalline oxygen reduction reaction catalysts with high / low index crystal plane structure.

[0041] (1) Add 50 mg of carbon powder to 15 mL of benzyl alcohol and stir ultrasonically for 2 h to form a uniform suspension; then add 75 mg of iminodiacetonitrile, 2.99 mg of nickel (II) acetylacetonate and 35.56 mg of palladium (II) acetylacetonate to the above suspension and stir continuously for 6 hours until it is completely dissolved.

[0042] (2) The resulting solution was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 140°C for 6 hours. Afterwards, the intermediate product was separated by centrifugation and washed three times with ethanol and acetone. Finally, the temperature was increased at a rate of 5°C / min and 10 wt% H 2 / Ar atmosphere, and calcined at 700℃ for 4h to obtain the final product, a PdNi alloy nanocrystalline electrode material with a high / low index crystal plane structure.

[0043] Example 2

[0044] The PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure prepared in Example 1 was used to prepare a fuel cell cathode oxygen reduction reaction electrode and test its oxygen reduction performance.

[0045] Take 2 mg of the PdNi alloy nanocrystalline electrode material with high / low index crystal plane structure prepared in Example 1 and disperse it in a mixed solution of 408 μL ultrapure water, ethanol and Nafion (5wt%) solution (the ratio of ethanol to ultrapure water is 1:1, and Nafion is 8 μL), then drop 14 μL of ink on the RDE and dry it naturally. A glassy carbon rotating disk electrode (RDE) with a diameter of 5 mm was used as the working electrode, a platinum sheet was used as the counter electrode, and saturated Ag / AgCl was used as the reference electrode. CV, LSV, methanol resistance test and accelerated degradation test (ADT) were carried out in a 0.1 mol / L KOH solution in the potential range of 0.05-1.2 V vsRHE. The electron transfer number (n) and hydrogen peroxide yield (H) were measured on CHI 760 using a rotating return disk electrode (RRDE). 2 O 2 %) determination.

[0046] Figure 1 This is the XRD pattern of the PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure obtained in Example 1. It can be seen that the material has a good cubic phase (fcc) crystal structure, and is shifted to a high diffraction angle compared to the PDF standard card corresponding to Pd, and the diffraction peak is located between Ni and Pd, indicating that it is a typical alloy structure.

[0047] Figure 2 TEM image of the PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure obtained in Example 1. From TEM and HRTEM, we can see that the polydispersed PdNi nanoparticles, the Pd lattice is compressed, the surface is rough and there are many Pd high index crystal planes (for example: 200, 220, 211 and 311), in a state of high / low index crystal plane coexistence. From its mapping and line scan, we can see that Pd, Ni, and N are evenly distributed in the PdNi nanoparticles.

[0048] Figure 3 The XPS graph of the PdNi alloy nanocrystal oxygen reduction reaction catalyst with high / low index crystal plane structure obtained in Example 1. It can be seen that Pd, Ni, N, and C elements exist in the PdNi nanoparticles, among which Pd is mainly in the form of Pd 0 Ni exists in the form of Ni 2+ C is a graphene-like electronic structure arrangement, and there are 4 different types of nitrogen.

[0049] Figure 4Example 2 is a PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure in N 2 CV graphs measured in saturated 0.1 mol / L KOH solution. All curves detected the presence of 8 redox peaks, and the reduction peaks were strong and sharp, indicating that the material has good ORR potential.

[0050] Figure 5 This is a comparison chart of the LSV and ORR performance of PdNi alloy nanocrystalline oxygen reduction reaction catalysts with different palladium and nickel ratios in Example 2. It can be seen that when the atomic ratio of Pd to Ni is 10:1, the PdNi alloy nanocrystalline material presents the optimal half-wave potential and limiting diffusion current density, and has the optimal ORR performance.

[0051] Figure 6 The PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure in Example 2 is 2 Multiple LSV plots measured in saturated 0.1 mol / L KOH solution. It can be seen that the alloy nanocrystals have stable ORR activity, with a half-wave potential of about 0.892 mV and a limiting diffusion current density of about 0.525 mA / cm -2 .

[0052] Figure 7 The PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure in Example 2 is 2 The electron transfer number (n)-hydrogen peroxide yield plot (H 2 O 2 %). It can be seen that in the potential range of 0.1-0.8 V (vs. RHE), the number of electron transfers is 3.85-3.94, and the hydrogen peroxide yield is less than 7%, which is a typical "four-electron" transfer process.

[0053] Figure 8 This is a graph showing the methanol resistance of the PdNi alloy nanocrystals with high / low index crystal plane structures as oxygen reduction reaction catalysts in Example 2. After adding methanol, the current density of the PdNi alloy nanocrystals only slightly decays, indicating that it has excellent methanol resistance.

[0054] Fig. 9 The LSV graphs of the PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure in Example 2 before and after 10,000 accelerated degradation tests in 0.1 mol / L KOH solution. It can be seen that after 10,000 accelerated degradation tests, the half-wave potential of the PdNi alloy nanocrystalline oxygen reduction reaction catalyst with high / low index crystal plane structure only decays slightly, indicating that it has excellent oxygen reduction reaction stability.

[0055] It should be noted that, in the present invention, the amount of Pd, Ni metal precursor, solvent and iminodiacetonitrile added, reaction temperature, reaction time and other parameters can be adjusted accordingly according to common knowledge.

[0056] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A method for preparing a PdNi alloy nanocrystalline oxygen reduction reaction catalyst having a high / low index crystal plane structure, characterized in that: (1) Preparation of PdNi nanoparticles by solvothermal method; (2) The PdNi nanoparticles obtained in step (1) are subjected to a high-temperature calcination method to prepare a PdNi alloy nanocrystalline electrode material having a high / low index crystal plane structure.

2. As described in claim 1, taking metal precursors of Pd and Ni with different atomic ratios as an example, a method for preparing a PdNi alloy nanocrystalline oxygen reduction reaction catalyst with a high / low index crystal plane structure is characterized by: (1) PdNi nanoparticles were prepared as reaction intermediates by solvothermal method; (2) The intermediate product obtained in step (1) is placed in a tube furnace, and a PdNi alloy nanocrystalline electrode material with a high / low index crystal plane structure is prepared by a high-temperature calcination method.

3. The method for preparing the PdNi alloy nanocrystalline oxygen reduction catalyst with a high / low index crystal plane structure according to claim 2, characterized in that: In step (1), a certain amount of carbon powder is first dispersed in a certain amount of organic solvent and stirred continuously, and then a certain amount of Pd, Ni metal precursor and reducing agent are added to the above solution and stirred continuously. Then the completely dispersed suspension is transferred to a high-temperature reactor and placed in a blast drying oven for high-temperature reaction. Thereafter, the reactor is allowed to cool naturally, and the PdNi nanoparticles in the reactor are washed with ethanol and acetone and placed in a blast drying oven for drying.

4. The method for preparing the PdNi alloy nanocrystalline oxygen reduction catalyst with a high / low index crystal plane structure according to claim 2, characterized in that: In step (2), the PdNi nanoparticles obtained in step (1) are placed in a tubular furnace and calcined at a high temperature in a H2 / Ar atmosphere at a certain heating rate.

5. The method for preparing the PdNi alloy nanocrystalline oxygen reduction catalyst with a high / low index crystal plane structure according to claim 2, characterized in that: The Pd and Ni metal precursors used in the step 1) are Pd(acac)2 and Ni(acac)2, respectively, the reducing agent is iminodiacetonitrile, and the organic solvent is benzyl alcohol. First, a certain amount of carbon powder is added to the benzyl alcohol solvent under ultrasonic stirring, ultrasonic for 15 to 30 minutes, and then stirred for 1 to 2 hours after ultrasonic dispersion to form a uniformly dispersed suspension; then iminodiacetonitrile, Pd(acac)2 and Ni(acac)2 are added to the above suspension and stirred for 4 to 6 hours until completely dissolved, with a rotation speed of 1000 to 1600 rpm.

6. The method for preparing the PdNi alloy nanocrystalline oxygen reduction catalyst with a high / low index crystal plane structure according to claim 2, characterized in that: In the step 1), the mass and volume ratio of carbon powder and benzyl alcohol is 3 to 3.6; the mass of iminodiacetonitrile is 1.3 to 2 times that of Pd(acac)2 and Ni(acac)2, and the atomic ratio of Pd(acac)2 and Ni(acac)2 is (1 to 20):

1.

7. The method for preparing the PdNi alloy nanocrystalline oxygen reduction catalyst with a high / low index crystal plane structure according to claim 2, characterized in that: The suspension obtained in step 1) is transferred to a 25-100 mL stainless steel autoclave lined with polytetrafluoroethylene, placed in a forced air drying oven, and reacted at 130° C. to 160° C. for 5 to 7 hours. Then, the PdNi nanoparticles obtained by the reaction are centrifuged at a speed of 8000 to 12000 rpm and washed with ethanol and acetone.

8. The method for preparing the PdNi alloy nanocrystalline oxygen reduction catalyst with a high / low index crystal plane structure according to claim 2, characterized in that: The PdNi nanoparticles obtained by centrifugation in step 1) are first added with ethanol and ultrasonically treated for 2 to 8 minutes, then with acetone and ultrasonically treated for 2 to 8 minutes, centrifuged at a speed of 8000 to 12000 rpm, and washed and purified repeatedly for 2 to 5 times. The volume ratio of ethanol to acetone is 0.75 to 1.

5. Then, the purified PdNi nanoparticles are placed in a blast drying oven, dried at a temperature of 60 to 80° C. for 6 to 8 hours, and allowed to stand for 8 to 24 hours.

9. The method for preparing the PdNi alloy nanocrystalline oxygen reduction catalyst with a high / low index crystal plane structure according to claim 2, characterized in that: The PdNi nanoparticles obtained in step 2) are placed in a tubular furnace for high-temperature calcination, the calcination temperature is 600-800°C, the annealing time is 3-6 hours, the heating rate is 5-10°C / min, and the proportion of H2 in the H2 / Ar mixed gas is 5-10wt%.

10. Use of the PdNi alloy nanocrystalline electrode material with high / low index crystal plane structure according to claims 5-9 in the cathode oxygen reduction reaction of a fuel cell.